1995
DOI: 10.1136/thx.50.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Adult and paediatric size bronchoscopes for bronchoalveolar lavage in mechanically ventilated patients: yield and side effects.

Abstract: Background -Bronchoalveolar lavage is considered a safe procedure. When performed in the mechanically ventilated patient, however, potentially harmful effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…The results showed moderate but not significant reductions in Pa,O 2 . Several studies have evaluated oxygenation parameters in mechanically ventilated patients after BAL [17][18][19][20][21][22][23]. However, results are conflicting, as some authors reported a significant decrease in oxygenation, while others noted no such effects when different ventilator settings were adapted and FI,O 2 was increased during the bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed moderate but not significant reductions in Pa,O 2 . Several studies have evaluated oxygenation parameters in mechanically ventilated patients after BAL [17][18][19][20][21][22][23]. However, results are conflicting, as some authors reported a significant decrease in oxygenation, while others noted no such effects when different ventilator settings were adapted and FI,O 2 was increased during the bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…However, these problems occur if the bronchoscope reduces the diameter of the endotracheal tube by more than 50 % [27]. We employed pressure controlled ventilation to maintain opening pressures and avoid alveolar collapse during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Many retrospective studies have been done examining the adverse effects and complications of bronchoscopy during the procedure, almost all focusing directly on alterations in arterial blood gas values and hemodynamics, occurring secondary to BAL and transbronchial biopsy procedures. [5][6][7][8][9][10][11][12][13][14][15] Tension pneumothorax and death have been reported as complications of bronchoscopy in patients receiving mechanical ventilation. 1,8,14 Ricou et al 5 compared BAL results, tidal volume (Vt) reduction, and intratracheal pressure changes in a group of 20 adult patients receiving mechanical ventilation, in whom paired bronchoscopies were performed using an adult (5.9-mm outside diameter [OD]) vs a pediatric (3.4-mm OD) bronchoscope.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] Tension pneumothorax and death have been reported as complications of bronchoscopy in patients receiving mechanical ventilation. 1,8,14 Ricou et al 5 compared BAL results, tidal volume (Vt) reduction, and intratracheal pressure changes in a group of 20 adult patients receiving mechanical ventilation, in whom paired bronchoscopies were performed using an adult (5.9-mm outside diameter [OD]) vs a pediatric (3.4-mm OD) bronchoscope. BAL recovery compared favorably between the two bronchoscopes, Vt was reduced 46% with the adult bronchoscope and 38% with the pediatric bronchoscope, while intratracheal pressure increased 16% with the adult bronchoscope vs 0% with the pediatric bronchoscope.…”
mentioning
confidence: 99%